Perancangan Website Sekolah SMK Al-Islam Surakarta Dengan Wordpress - Susanto, Alip; , Dr. Heru Supriyono, M.Sc (2016)
Al-Islam Vocational High School of Surakarta is a is one of the establishments in the world of education. Al-Islam Vocational High School of Surakarta were under the guidance of university Al-Islam Foundation Surakarta which was established in September 13, 2008. During this time, Al-Islam Vocational High School very difficult to introduce themselves to the general public because the information is delivered only through leaflets, Al-Islam Vocational High School of Surakarta does not have an information system that can be accessed anytime. Therefore, the authors are interested in making an application website at Al-Islam Vocational High School of Surakarta. With the application of this website is expected Al-Islam Vocational High School of Surakarta can provide information easily. Information about Al-Islam Vocational High School of Surakarta can be easily accessed at any time by the public. The making of this website are using Wordpress CMS. The method used is the experimental methods and in-depth qualitative interviews with potential users. Designed website consisting of several pages, including homepage, profile, facilities, news, agenda, achievements, and contacts. The designed of this website is carried out fully so as to cover all the needs and solve all the problems such as the purpose of the application of this website.